Can single disease payment system based on clinical pathway reduce hospitalization costs in rural area? A case study of uterine leiomyoma in Anhui, China - Jing Peng; Mengran Zhang; Pingfeng Yu; Nan Wang (BMC, 2018)
Abstract Background Single disease payment program based on clinical pathway (CP-based SDP) plays an increasingly important role in reducing health expenditure in china and there is a clear need to explore the scheme from different perspectives. This study aimed at evaluating the effect of the scheme in rural county public hospitals within Anhui, a typical province of China,using uterine leiomyoma as an example. Methods The study data were extracted from the data platform of the New Rural Cooperative Medical Office of Anhui Province using stratified-random sampling. Means, constituent ratios and coefficients of variations were calculated and/or compared between control versus experiment groups and between different years. Results The total hospitalization expenditure (per-time) dropped from 919.08 ± 274.92 USD to 834.91 ± 225.29 USD and length of hospital stay reduced from 9.96 ± 2.39 days to 8.83 ± 1.95 days(P < 0.01), after CP-based SDP had implemented. The yearly total hospitalization expenditure manifested an atypical U-shaped trend. Medicine expense, nursing expense, assay cost and treatment cost reduced; while the fee of operation and examination increased (P < 0.05). The expense constituent ratios of medicine, assay and treatment decreased with the medicine expense dropped the most (by 4.4%). The expense constituent ratios of materials, ward, operation, examination and anesthetic increased,with the examination fee elevated the most (by 3.9%).The coefficient of variation(CVs) of treatment cost declined the most (− 0.360); while the CV of materials expense increased the most (0.186). Conclusion There existed huge discrepancies in inpatient care for uterine leiomyoma patients. Implementation of CP-based SDP can help not only in controlling hospitalization costs of uterine leiomyoma in county-level hospitals but also in standardizing the diagnosis and treatment procedures.